Preparation and in vivo evaluation of glyco-gold nanoparticles carrying synthetic mycobacterial hexaarabinofuranoside - Burygin, Gennady L.; Abronina, Polina I.; Podvalnyy, Nikita M.; Staroverov, Sergey A.; Kononov, Leonid O.; Dykman, Lev A. (Beilstein Journal of Nanotechnology, 2020)
A number of bacterial glycans are specific markers for the detection and the serological identification of microorganisms and are also widely used as antigenic components of vaccines. The use of gold nanoparticles as carriers for glyco-epitopes is becoming an important alternative to the traditional conjugation with proteins and synthetic polymers. In this study, we aimed to prepare and evaluate in vivo glyco-gold nanoparticles (glyco-GNPs) bearing the terminal-branched hexaarabinofuranoside fragment (Ara6) of arabinan domains of lipoarabinomannan and arabinogalactan, which are principal polysaccharides of the cell wall of Mycobacterium tuberculosis, the causative agent of tuberculosis. In particular, we were interested whether the antibodies generated against Ara6-GNPs would recognize the natural saccharides on the cell surface of different mycobacterial strains. Two synthetic Ara6 glycosides with amino-functionalized spacer aglycons differing in length and hydrophilicity were directly conjugated with spherical gold nanoparticles (d = 15 nm) to give two sets of glyco-GNPs, which were used for the immunization of rabbits. Dot assays revealed cross-reactions between the two obtained antisera with the hexaarabinofuranoside and the 2-aminoethyl aglycon used for the preparation of glyco-GNPs. Both antisera contained high titers of antibodies specific for Mycobacteria as shown by enzyme-linked immunosorbent assay using M. bovis and M. smegmatis cells as antigens while there was only a weak response to M. phlei cells and no interaction with E. coli cells. The results obtained suggest that glyco-GNPs are promising agents for the generation of anti-mycobacterial antibodies.
Keywords: conjugation of glycosides; gold nanoparticles; lipoarabinomannan; Mycobacterium; spacer aglycon